Sedum keniense (Crassulaceae), a new species from Mt. Kenya, East Africa - Zhou, Ya-Dong; Hu, Guang-Wan; Yan, Xue; Mwachala, Geoffrey; Gituru, Robert Wahiti; Wang, Qing-Feng (Phytotaxa, 2016)
Here we report a new species of Crassulaceae, Sedum keniense, from the high elevation region of Mt. Kenya in East Africa. Sedum keniense is easily recognizable by its farinose stems and leaves, as well as comparatively larger inflorescences and flowers. It is similar to S. ruwenzoriense and S. meyeri-johannis, both of which are widely distributed at high elevations on most mountains in tropical East Africa.